Antimicrobial resistance in community-acquired enteric pathogens among children aged ≤ 10-years in low-and middle-income countries: a systematic review and meta-analysis - Okumu, Noah O.; Muloi, Dishon M.; Moodley, Arshnee; Watson, Julie; Kiarie, Alice; Ochieng, Linnet; Wasonga, Joseph O.; Mutisya, Christine; Alumasa, Lorren; Ngeranwa, Joseph J. N.; Cumming, Oliver; Cook, Elizabeth A. J. (Frontiers in Microbiology, 2025)
IntroductionAntimicrobial resistance (AMR) is a global health priority. This systematic review summarizes the prevalence of AMR in enteric pathogens originating from the community, specifically among ≤10-year-old children in low-and middle-income countries (LMICs). In addition, it presents the proportions of pooled resistance in Campylobacter spp., Escherichia coli, Shigella spp., and Salmonella spp. (CESS) to clinically relevant antibiotics.MethodsSix online repositories, namely PubMed, Medline, Web of Science, Cochrane Library, CABI, and EMBASE were searched for articles published between January 2005 and September 2024. Random-effects meta-analysis models were constructed to estimate the pooled AMR proportions for CESS pathogens, and a subgroup analysis by region was also carried out.ResultsA total of 64 publications from 23 LMICs met our inclusion criteria. The pooled estimates of E. coli AMR for clinically important antibiotics were as follows: sulfamethoxazole/trimethoprim (SXT) 71% [95%CI: 57–82%]; ampicillin (AMP) 56% [95%CI: 44–67%]; ciprofloxacin (CIP) 10% [95%CI: 5–20%]; and ceftriaxone (CRO) 8% [95%CI: 2–31%]. The proportions of AMR detected in Shigella spp. were AMP 76% [95%CI: 60–87%]; nalidixic acid (NA) 9% [95%CI: 2–31%]; CIP 3% [95%CI: 0–15%]; and CRO 2% [95%CI: 0–19%]. The proportions of Salmonella spp. AMR were AMP 55% [95%CI: 35–73%] and SXT 25% [95%CI: 15–38%]. The proportions of Campylobacter spp. AMR were erythromycin (ERY) 33% [95%CI: 12–64%] and CIP 27% [95%CI: 8–61%]. There was high variability in the regional subgroup analysis, with high interstudy and regional heterogeneity I2 ≥ 75%.ConclusionOur results shed light on drug-resistant enteric bacterial pathogens in young children, providing evidence that CESS pathogens are becoming increasingly resistant to clinically important antimicrobials. Regional differences in resistance patterns between these community isolates highlight the need for strong national and regional surveillance to detect regional variations and inform treatment and appropriate antibiotic stewardship programs. The limitations of our findings include high regional variability, significant interstudy heterogeneity, and underrepresentation of certain LMICs.Systematic review registrationhttps://inplasy.com/inplasy-2024-2-0051/, registration number: INPLASY202420051.